User Acceptance Of The Speedcash Digital Wallet Using Tam - Laura Naily Tsabita; Dwi Fatrianto Suyatno (CV. SINAR HOWUHOWU, 2026)
The rapid growth of digital wallet services highlights the importance of understanding factors influencing user acceptance of financial technology applications. This study aims to analyze the level of technology acceptance of the SpeedCash digital wallet application using the Technology Acceptance Model (TAM). A quantitative approach was employed by distributing questionnaires to SpeedCash users selected through purposive sampling. The variables examined include Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual Usage (AU). Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), including validity testing, reliability testing, outer model evaluation, and inner model evaluation. The results indicate that Perceived Ease of Use has a positive and significant effect on both Perceived Usefulness and Attitude Toward Using. Perceived Usefulness also positively influences Attitude Toward Using. Furthermore, Attitude Toward Using positively affects Behavioral Intention to Use, while Behavioral Intention to Use positively affects Actual Usage. The findings demonstrate that perceived ease of use and perceived usefulness are the primary factors shaping users’ attitudes, intentions, and actual usage of the SpeedCash application. Therefore, improving service quality through user-friendly features and providing tangible benefits to users can enhance technology acceptance of the SpeedCash digital wallet application.